Empty Chair Technical Group Guidance and Self Talk Improve Interpersonal Communication Skills - Fauzi Aldina; Teuku Fadhli (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to examine the impact of empty chair technique group guidance and self-talk techniques to improve interpersonal communication skills of students at SMA Unggul Sigli. The research method used was experimental design, randomized pretest-posttest comparison group design involving 20 research subjects who were selected proposively from 82 students. The results showed that the empty chair technique and self-talk technique were effective to improve students' interpersonal communication skills with the difference in the level of effectiveness of the self-talk technique group counseling higher than the empty chair technique. Empty chair technique group guidance and self-talk techniques are effective to improve interpersonal communication skills of SMA Unggul Sigli students.